Techno-Economic Assessment Of Sensor-Enabled Sugarcane Planters Using Battery And Pto Mechanisms - Mishra, Ashutosh; Pal, Ramesh; Shahi, N.C.; Singh, Priyanka; Kumar, Aviral (Journal of Neonatal Surgery, 2025)
This study examines all the key technical and financial factors for battery and PTO powdered sugarcane planters, to boost mechanized planting in developing farming regions. Normally, sugarcane, used both for sugar and bio-energy, is planted in a way that takes more effort and this approach leads to gaps in coverage and greater costs. Pairing sensors with batteries and Power Take Offs in planters can greatly improve planting results, productivity and concern for the environment. By using the Co 6304 variety in carefully conducted field experiments, this research assesses the set length, planting depth, bud damage, soil potassium levels and various trash removal techniques at different speeds. It also examines how much each type of power mechanism costs, how much energy is consumed, how much labor is needed and how effectively they work in fields, giving useful suggestions to farmers, manufacturers and policy decision-makers. It was clear from these findings that improved planting evenness and efficiency can result from using sensors in equipment and trash left on the soil boosts potassium levels, encouraging healthier crops. The importance of both performance and affordability for machines suggests that advanced systems may aid in modernizing sugarcane farms, lower manual work and help farms use resources more efficiently.